Gaining Cultural Intelligence through Second Life Learning Interventions - Siegel, Sarah Ellin (International Journal of Advanced Corporate Learning (iJAC), 2010)
Companiesâ?? investment in international assignments remains essential, but is affordable for only relatively few employees. In todayâ??s global economy, many employees must gain cultural intelligence. Encyclopedic web sites and smart game simulations are ill-equipped to offer the live, authentic immersive experience of Virtual World environments; learning from colleagues who are country-natives through interacting with them in a Virtual World like Second Life is the next best thing to being there, and it requires no travel. Virtual world learning sessions with local ambassadors are affordable on a massive scale compared with international assignments. In addition, through Virtual World experiences, international assignees can be more effective with colleagues from their assigned countries prior to boarding planes, even prior to Day 1 of the assignment. This research proposal, including a literature review and a research design, asks, and begins to answer: What can cultural intelligence learning in Second Life achieve or advance that cultural intelligence learning in real-life within the cultures, smart game simulations and encyclopedic, self-service web sites cannot as readily?